2016
DOI: 10.1177/0010414016633224
|View full text |Cite
|
Sign up to set email alerts
|

Economic Hardship and Policy Preferences in the Eurozone Periphery

Abstract: What is the impact of economic suffering on support for euro membership and austerity policies in the Eurozone periphery? This article uses original public opinion and firm surveys conducted in Spain in the midst of the great recession to describe the structure of preferences toward the euro as a common currency and austerity policies, focusing on the specific impact of crisis exposure. We find that in spite of the depth and the duration of the economic crisis, support for Spain’s membership in the Eurozone is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 35 publications
(45 reference statements)
2
35
0
7
Order By: Relevance
“…The financial crisis of 2008 and its aftermath have fundamentally shaken the European political system. As a range of scholars have shown, the strains caused by the crisis have brought about important changes in the way citizens perceive the EU project and its key financial institutions (Fernández‐Albertos & Kuo ; Hobolt & De Vries ). These changes have also affected the way voters approach the question of what their country should do, if at all, to help other EU countries in economic distress.…”
Section: Discussionmentioning
confidence: 99%
“…The financial crisis of 2008 and its aftermath have fundamentally shaken the European political system. As a range of scholars have shown, the strains caused by the crisis have brought about important changes in the way citizens perceive the EU project and its key financial institutions (Fernández‐Albertos & Kuo ; Hobolt & De Vries ). These changes have also affected the way voters approach the question of what their country should do, if at all, to help other EU countries in economic distress.…”
Section: Discussionmentioning
confidence: 99%
“…Support for the euro has remained remarkably high in all Eurozone countries throughout the crisis (Hobolt & Wratil 2015, Roth et al 2015. Although in deficit states most people express a preference for the rather impossible crisis strategy of keeping the euro and ending austerity at the same time (Clements et al 2014, Fernández-Albertos & Kuo 2016, they have shown a strong preference for the euro when pressed to choose between the two (Dinas et al 2016).…”
Section: Domestic Crisis Resolution: Politics Within Countriesmentioning
confidence: 99%
“…Broadly speaking, the data above highlight the need for further examination of potential wide-ranging implications associated with tough economic climates. Empirical research has mainly focused on investigating the socioeconomic and political impacts of the global economic downturn [10][11][12][13], while analysis of its psychological repercussions has captured relatively little scholarly attention. Overall, within this framework, most studies have given a special focus to the effects of the economic crisis on psychological well-being and healthrelated indicators.…”
Section: Introductionmentioning
confidence: 99%